A Preliminary Study of the Application of Electromagnetic Conductivity Meter on Soil Properties of Paddy Cultivation Areas at Wue Village, Jantho, Aceh Besar District, Indonesia - . Marwan (Graduate Program of Syiah Kuala University, 2015)
Conventional soil sampling is time consuming and requires meticulous laboratory analysis. Hence, mapping of soil apparent in respect to electrical conductivity (ECa) has been developed to identify areas of contrasting soil properties. Such ECa values are represent measures of soil properties. The sensor system, GF Instrument model CMD-4 were used to analyze soil physical properties. This system consists of three important parts, ECa sensor, data logger and Global Positioning System (DGPS) receiver. This research was aimed to evaluate the relationships between ECa and soil properties as well as the yield of rice (paddy) in paddy’s farming fields. One study site was chosen. The sensor was pulled through a plotted area of 0.25 km2. The distribution map of ECa was developed to identify the contrast of ECa. More than 100 ECa of data points were collected in 3-hour for the large plot. The data was later transferred to a notebook computer for generation of ECa maps using Surfer 11 software. According to the data analyses, field and ECa showed positive correlation. The average values of ECa are significantly different between hilly area and drainage canal area signifying differences in soil structure. Soil ECa could provide a measure of the spatial differences associated with soil physical and chemical properties, which for paddy soil may be a measure of soil suitability for crop growth and its productivity. This sensor can measure the soil ECa through the field quickly for detailed features of the soil and can be operated by just one worker. The ECa map provides some ideas for future soil management